Strategic prioritization of blockchain diffusion factors by an integrated fuzzy Delphi-Dombi LMAW model: A case study in Bangladesh healthcare sectors - Nasif Morshed; Raad Shahamat Labib; Mushfiqur Rahman; Kazi Md. Tanvir Anzum (PLoS ONE, 2026)
Over the recent years, blockchain technology has been an essential practice in enhancing profitability in healthcare supply chains, especially in emerging economies. Nevertheless, regulatory uncertainty, management resistance and inadequate technological infrastructure are major setbacks. This study evaluates the diffusion factors of blockchain technology in healthcare sector of Bangladesh within a two-stage method; first, combining literature review and expert opinions, 26 significant factors were identified, which were later reduced to 22 through Fuzzy Delphi Method across 5 dimensions (Organizational, Technological, Environmental, Managerial, Individual). In the second stage, the factors ranked in importance using the Dombi Logarithmic Methodology of Additive Weights (LMAW) were consequently subjected to sensitivity analysis to ensure the robustness of results. The results indicate that the most impactful drivers are Top Management Support (0.0501), Organization Readiness (0.0485) and Trust Among Stakeholders (0.0481) for all the healthcare organizations whereas Smart Contract Automation (0.0368) and Innovation Pressure (0.0362) got the least importance and indicate that the sector is in need of strategic leadership and infrastructure rather than advanced innovations. Theoretically, this study advances technology adoption literature by demonstrating that fundamental organizational readiness and leadership support act as non-compensatory prerequisites for blockchain diffusion in emerging economies. Managerially, the proposed framework empowers healthcare executives and policymakers with an actionable roadmap for targeted resource allocation, facilitating strategic blockchain integration to enhance supply chain transparency and resilience.